Exclusão de mulheres no texto bíblico - Leite, Maria da Penha (2020)
Social relations, over the years have undergone reformulations, whereas biblical texts have remained with their appearance and essence the same as they were at the time they were written. Thus, biblical texts, specifically parables, were and still are used for missionary purposes, using literary strategies, such as satire, to achieve the goals of religious teachings.Those are narratives that adress the emergence of human existence, based on myths and legends to justify the existence of the divine. However, as these texts are responsible for the formation of the social imaginary, they have contributed and continue to contribute to the naturalization of violence and exclusion of women. In this research the biblical text was used as an object of analysis. For this purpose, contributions from authors who have already written about it were necessary, which allowed a broader view of religious phenomena, giving importance to education that contributes to the conscious formation of their performance in a society that every minute, updates its knowledge and modernization, thanks to information technologies. It was discussed about textual productions such as the parable, the historical contextualization of texts and contemporary history, because according to the reading of these narratives and the research carried out by other authors, it is possible to deconstruct certain already common views and develop biblical messages that do not: contribute to false interpretations, validate violence against women and encourage the situation of submission and subservience by the female figure.